2009
DOI: 10.1016/j.ejvs.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for the Prevention of Infection after Major Limb Amputation

Abstract: It is agreed that prophylactic antibiotics are part of the standard of care for amputation surgery, and this is supported by limited, mostly historical-controlled data. Evolution of the bacterial threat means that future studies should assess the role and type of prophylaxis for patients with existing bacterial colonisation or infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Post-procedural doses of intravenous antibiotics (up to 24 hours) are only required in defined circumstances, such as some cardiac and vascular surgeries, and lower limb amputation. [38][39][40] The 2016 Surgical National Antimicrobial Prescribing Survey found that incorrect duration was the most common factor in inappropriate post-procedural antimicrobial prescribing (73.7%). 7 Prophylaxis should not extend beyond 24 hours, regardless of the surgical procedure.…”
Section: Right Durationmentioning
confidence: 99%
“…Post-procedural doses of intravenous antibiotics (up to 24 hours) are only required in defined circumstances, such as some cardiac and vascular surgeries, and lower limb amputation. [38][39][40] The 2016 Surgical National Antimicrobial Prescribing Survey found that incorrect duration was the most common factor in inappropriate post-procedural antimicrobial prescribing (73.7%). 7 Prophylaxis should not extend beyond 24 hours, regardless of the surgical procedure.…”
Section: Right Durationmentioning
confidence: 99%
“…Severe stump wound infection is a common cause of failure of amputation and results in need for stump revision or re-amputation. This further surgical procedure exposes susceptible patients to the risk of operative surgical intervention and other serious complications [4,9]. Extremity amputation is a common life-saving procedure in the management of victims of natural disasters and mass casualties with severely injured limbs [5,6,14,19].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of evidence-based guidelines for use of antimicrobials had been shown to improve the overall patient outcome. Studies [4,5] have established the efficacy of surgical antibiotic prophylaxis for reducing the risk of postoperative wound infection. Others have consistently shown an association between timely start of antibiotics for patients with serious infections and a favorable clinical outcome [6,7,8].…”
Section: Introductionmentioning
confidence: 99%